Integrated rural development in the Philippines the coordination problem - Aminuzzaman, Salahuddin (1982)
The integrated approach to rural development is distinguished as a conspicuous concern in the field of public administration vis-a-vis the development agenda of Third World countries. Different approaches and models on rural development programs have been adopted by the developing countries from the Western countries' expertise only to discover that disparities in terms of context and background encumber the applicability of such models. It is imperative, therefore, that selection of a particular method should depend on the existing political, economic, cultural, and social conditions of the country involved. Integrated rural development (IRD) as an approach basically requires the achievement of two broad objectives: (1) a coordinated and concerted effort of comprehensive development for the rural areas; and (2) the creation of an institutional base at the grassroot level to ensure effective participation. The nature of IRD programs demands a wide variety of administrative policy, financial and technical inputs, and at the same time increases pressure on national government planning and organizational machinery. These activities have generated* multifarious problems, one of which is the problem of coordination. Lack of coordination is identified as a chronic issue plaguing rural development planning. Thus, attempts have' been directed towards the coordination and integration of development efforts through the enactment and creation of laws and implementing agencies, respectively, deemed to be supportive to carry out such activities.
Keywords: Rural development -- Government policy; Integrated Rural Development (IRD); Coordination (Human services)